Performance measurements and analysis of bluetooth low energy - LINHARES, André Guedes (2016)
The Internet of Things (IoT) paradigm has been rapidly gaining ground in the academic and industry communities as one of the most important emerging technologies. Some wireless communication technologies such as Bluetooth Low Energy (BLE) have been pointed as key technologies that will drive IoT applications. In order to leverage the BLE technology in IoT applications and identify the niche of applications this technology is more suitable, it is essential we have a deep understanding regarding some features such as link capacity, data transfer delay, connection establishment latency, and power consumption. This work evaluates the networking capabilities from BLE in scenarios of data transfer and connection establishment. The metrics maximum throughput, one-way delay, round-trip time, and connection establishment latency are evaluated through experimental measurements and we investigate how some factors (e.g. connection interval, pairing, packet size) impact on these metrics. Finally, this work proposes analytical models for the metrics investigated.